2009
DOI: 10.1172/jci39054
|View full text |Cite
|
Sign up to set email alerts
|

MAPK phosphatase-1 facilitates the loss of oxidative myofibers associated with obesity in mice

Abstract: Oxidative myofibers, also known as slow-twitch myofibers, help maintain the metabolic health of mammals, and it has been proposed that decreased numbers correlate with increased risk of obesity. The transcriptional coactivator PPARγ coactivator 1α (PGC-1α) plays a central role in maintaining levels of oxidative myofibers in skeletal muscle. Indeed, loss of PGC-1α expression has been linked to a reduction in the proportion of oxidative myofibers in the skeletal muscle of obese mice. MAPK phosphatase-1 (MKP-1) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
90
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(97 citation statements)
references
References 62 publications
4
90
2
1
Order By: Relevance
“…[45][46][47][48] In contrast to the well-defined role of MPK-1 in the inflammatory response to paracrine pathway. Previous studies have suggested that MKP-1 has a function in myogenesis; 47,[51][52][53] however, distinctions between our results and the previously reported findings could be due to the different experimental models used in the referred studies, thereby understriking the need for a future evaluation of MKP-1 function using muscle-specific deletion approaches.…”
Section: The Inflammatory Response To Tissue Damagecontrasting
confidence: 93%
“…[45][46][47][48] In contrast to the well-defined role of MPK-1 in the inflammatory response to paracrine pathway. Previous studies have suggested that MKP-1 has a function in myogenesis; 47,[51][52][53] however, distinctions between our results and the previously reported findings could be due to the different experimental models used in the referred studies, thereby understriking the need for a future evaluation of MKP-1 function using muscle-specific deletion approaches.…”
Section: The Inflammatory Response To Tissue Damagecontrasting
confidence: 93%
“…Overexpression of MKP-1 in adult type IIb (glycolytic) myofibers converts these fibers to slower-twitch type IIa or type I (oxidative) fibers, suggesting that MKP-1-mediated dephosphorylation of MAPK signaling is required to maintain the glycolytic fiber phenotype through the repression of slow myofibers (Shi et al, 2008). Consistent with these data, it has been shown that MKP-1-deficient mice are protected from the loss of oxidative myofibers during high fat diet-induced obesity (Roth et al, 2009). Hence, decreased MKP-1 expression results in enhanced MAPK signaling, which protects from the loss of glycolytic myofibers by driving oxidative myofiber conversion.…”
Section: Mkps In Skeletal Myogenesis and Skeletal Muscle Functionmentioning
confidence: 55%
“…We found that mdx/mkp-1 -/-mice have reduced body weight and muscle mass in comparison with mdx/mkp-1 +/+ mice (Shi et al, 2010). The reduction of body weight may be attributed to the chronic elevated levels of inflammation or it is also likely that this is due to an underlying metabolic defect that we have observed in mice lacking MKP-1 that is related to increased energy expenditure (Roth et al, 2009;Wu et al, 2006). Histological analysis of muscle sections from mdx/mkp-1 -/-mice revealed that MKP-1 deficiency exacerbates the pathogenesis of muscular dystrophy (Shi et al, 2010).…”
Section: Mkps In Skeletal Myogenesis and Skeletal Muscle Functionmentioning
confidence: 62%
See 1 more Smart Citation
“…In the central nervous system, MAPKs are required for proper neuronal axonal development [13]. MAPKs also play a critical part in energy metabolism through modulating lipid metabolism [14][15][16] and skeletal muscle growth and fiber type [6]. Given the fact that MAPKs play such a fundamental and integral role in a broad range of biological processes, interference of this pathway and their downstream effector proteins may have detrimental consequences leading to either metabolic disorder or diseases.…”
mentioning
confidence: 99%